Village Government Capacity in Increasing Village Original Income through Tourism Potential in Bua Village, Tellulimpoe District - Muhlis Hajar Adiputra; Khairul Insan; Madalle Agil; Mila Mey Murdiana (Jurnal Office, 2021)
Village Original Income or (PADes) according to Law No. 6 of 2014 is income that comes from village authority based on origin rights and local village scale. In an effort to develop PADes, it is necessary to carry out an economic empowerment where rural communities have the opportunity and freedom to develop their economy. This research uses the qualitative approach with research methods will be used. Informants in this research are the Head of Bua Village, Bua Village Officials, Head of Dusun, BPD, and Bua Village Community. Data analysis techniques are data collection, data reduction, data presentation and conclusion drawing. The results of the study through observations, interviews, and concluded that the capacity of the village government in increasing village original income through tourism potential in Bua village, Tellulimpoe sub-district, both from the level of skill, commitment, and awareness already exists, although it is not optimal, as expected because it takes time and is available. some of the obstacles faced, firstly, the Covid pandemic caused the budget for the development of bullokong beach attractions to be temporarily suspended.